Bioremediation of Phenol, Ammonia, Nickel, Hexavalent Chromium and Iron from Steel Plant Effluent of Visakhapatnam City by Live, Killed and Immobilized Bacteria - M. Elizabeth, K.; Esther Rani, G. (Asian Journal of Chemistry, 2016)
Bioremediation of phenol, ammonia, nickel, hexavalent chromium and iron from untreated steel plant effluent of Visakhapatnam city was carried out using different bacteria. Live Bacillus species could remove 8% phenol, 100% ammonia, 92.5% nickel, 88% hexavalent chromium and 73.1% iron(II), from industrial effluent. Biosorption technique showed 100% and 97% of chromium removal by Staphylococcus aureus and Bacillus species (BS2) respectively. There was 90.7 and 47.7 removal of ammonia by Bacillus species and Staphylococcus aureus respectively by immobilization technique. Chi-square test was employed to test whether the results obtained were significant or not at the level of P < 0.05.